Falling leaves the true story of an unwanted Chinese daughter - Mah, Adeline Yen 1937- (Broadway books, 1999)
A courgeous woman's triumph over despair in a lifelong search for acceptance, love, and understanding. Unfolding against a turbulent backdrop of social, political, and cultural upheaval, it is at once a work of heartfelt intimacy and a rare portrait of twentieth-century China.